2008
DOI: 10.1111/j.1471-0528.2008.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the ST‐interval segment of the fetal electrocardiogram in relation to acid–base status at birth

Abstract: Objective To assess the occurrence of ST-interval segment changes of the fetal electrocardiogram (ECG) and cardiotocographic (CTG) abnormalities preceding acidaemia at birth.Design Case-control study.Setting University hospital labour ward.Sample Newborns with severe cord artery metabolic acidaemia (pH < 7.00 and lactate ‡ 10 mmol/l; n = 24), moderate metabolic acidaemia (pH 7.00-7.09 and lactate ‡ 10; n = 48), acidaemia (pH 7.00-7.09; n = 52), pre-acidaemia (pH 7.10-7.19; n = 265), and controls (pH ‡ 7.20; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A CTG with normal variability and accelerations or a normal FBS is required at the start of monitoring for a confident evaluation of ST data, but even then hypoxia/acidosis can rarely develop during labor without the occurrence of ST events. Finally, ST events have been reported in about 50% of normally oxygenated fetuses, but only in 16% were they associated with abnormal CTG patterns warranting intervention according to the STAN guidelines [58].…”
Section: Limitations and Risksmentioning
confidence: 99%
“…A CTG with normal variability and accelerations or a normal FBS is required at the start of monitoring for a confident evaluation of ST data, but even then hypoxia/acidosis can rarely develop during labor without the occurrence of ST events. Finally, ST events have been reported in about 50% of normally oxygenated fetuses, but only in 16% were they associated with abnormal CTG patterns warranting intervention according to the STAN guidelines [58].…”
Section: Limitations and Risksmentioning
confidence: 99%
“…In the RCTs (33–37) and in the observational study by Norén et al (38), umbilical artery metabolic acidosis was defined as pH <7.05 and BE < −12 mmol/L. In the case–control study (39) lactate >10 mmol/L was used as a criterion instead of BE. A pH difference of at least 0.03 between artery and vein was used by Westerhuis et al (34,35) to ensure that one of the two samples was from the artery.…”
Section: Resultsmentioning
confidence: 99%
“…The case–control study (39) reported intervention rates in relation to different grades of fetal metabolic acidemia at birth. Intervention was recommended in 96% of the cases with severe metabolic acidemia and in 62% of the cases with moderate metabolic acidemia according to STAN® clinical guidelines, whereas the corresponding figures for CTG only were 92 and 46%.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper we calculated waveform-based ECG markers, during normoxemia and hypoxemia. Also, the absence of STAN-events due to poor signal quality in human fetuses associated with metabolic acidosis has been reported in literature [ 25 , 26 ]. We conclude that improvement of the algorithm might result in more sensitive event warning.…”
Section: Discussionmentioning
confidence: 99%